1992
DOI: 10.3109/00207459208987195
|View full text |Cite
|
Sign up to set email alerts
|

The Pineal Gland and the Menstrual Cycle

Abstract: The menstrual cycle reflects the expression of a cyclical process involving the interaction between the hypothalamic-pituitary axis and the ovaries. This complex process requires an integrated neural and humoral control mechanism. It is now well established that a hypothalamic "transducer" located in the medial basal hypothalamus integrates neural and humoral information and translates it into an oscillatory signal which eventually results in the release of the gonadotropin releasing hormone (GnRH), triggering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Animal studies have also shown that melatonin can inhibit luteinizing hormone-induced testosterone production in rats (16)(17)(18), inhibits prolactin cell activity in male and female hamsters (19), and suppresses several aspects of reproductive physiology in male hamsters (20). Human studies indicate that decreased concentrations of circulating melatonin (such as those brought about by circadian disruption) can result in increased release of the gonadotropins luteinizing hormone and follicle-stimulating hormone from the pituitary and estrogen release by the ovaries (21)(22)(23)(24)(25). There is also evidence from clinical studies of a relationship between melatonin and male reproductive hormones (26)(27)(28)(29).…”
Section: Cancer Epidemiol Biomarkers Prev 2008;17(12) December 2008mentioning
confidence: 99%
“…Animal studies have also shown that melatonin can inhibit luteinizing hormone-induced testosterone production in rats (16)(17)(18), inhibits prolactin cell activity in male and female hamsters (19), and suppresses several aspects of reproductive physiology in male hamsters (20). Human studies indicate that decreased concentrations of circulating melatonin (such as those brought about by circadian disruption) can result in increased release of the gonadotropins luteinizing hormone and follicle-stimulating hormone from the pituitary and estrogen release by the ovaries (21)(22)(23)(24)(25). There is also evidence from clinical studies of a relationship between melatonin and male reproductive hormones (26)(27)(28)(29).…”
Section: Cancer Epidemiol Biomarkers Prev 2008;17(12) December 2008mentioning
confidence: 99%
“…It is possible that the level of intrafollicular melatonin (not captured by the present study) is what supports the subsequent production of progesterone and stabilizes the CL. Another distinct function of melatonin may be to govern the menstrual cycle through its reciprocal relation with gonadotropin-releasing hormone pulse frequency [ 27 ]. The gonadotropin-releasing hormone pulse generator is slowest (approximately every 4-6 hours) in the late luteal phase, when melatonin is high, and is fastest (approximately circhoral) at midcycle, when melatonin is low [ 28 ].…”
Section: Discussionmentioning
confidence: 99%